1991
DOI: 10.1021/bi00227a026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a putative clone for the 67-kilodalton elastin/laminin receptor suggests that it encodes a cytoplasmic protein rather than a cell surface receptor

Abstract: The 67-kDa elastin binding protein shares many immunological and structural properties with the high-affinity 67-kDa tumor cell laminin receptor. Taking advantage of these similarities, we have screened a bovine cDNA library with a partial cDNA probe for the laminin receptor and have isolated and characterized a cDNA clone of 1038 bp that hybridizes to a single-size mRNA of 1.3 kb. The clone encodes a protein with a predicted molecular weight of 33K that lacks an N-terminal leader sequence, shows no posttransl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
3
27
0
2
Order By: Relevance
“…We next compared the cDNA sequence of the rat 40 kDa ribosomal protein with sequences in the EMBL data bank (release 30). The search revealed that the rat cDNA showed 52-95% identity with the cDNAs isolated as cell surface 68 kDa laminin binding protein cDNAs of human (88%) [17,18], mouse (95%) [19], bovine (88%) [20], Hydra vulgaris (54%) [21] and Drosophila melanogaster (52%) [22]. Since most of the base differences between the species were in the wobble position, the deduced amino acid sequence of the rat cDNA shared 99% identity with those of mammalian cDNAs (human, mouse and bovine) and 57-59% identity with those of cDNAs of hydra (59%) and drosophila (57%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next compared the cDNA sequence of the rat 40 kDa ribosomal protein with sequences in the EMBL data bank (release 30). The search revealed that the rat cDNA showed 52-95% identity with the cDNAs isolated as cell surface 68 kDa laminin binding protein cDNAs of human (88%) [17,18], mouse (95%) [19], bovine (88%) [20], Hydra vulgaris (54%) [21] and Drosophila melanogaster (52%) [22]. Since most of the base differences between the species were in the wobble position, the deduced amino acid sequence of the rat cDNA shared 99% identity with those of mammalian cDNAs (human, mouse and bovine) and 57-59% identity with those of cDNAs of hydra (59%) and drosophila (57%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vol. 11 1, 1996 previous studies that identified p40 in severa1 eukaryotic organisms as distant phylogenetically as plants (Axelos et al, 1993;García-Hernández et al, 1994), mammals (Makrides et al, 1988;McCaffery et al, 1990;Grosso et al, 1991), Hydra (Keppel and Schaller, 1991), Drosophila (Melnick et al, 1993), yeast (Davis et ai., 1992), and sea urchin (Rosenthal and Wordeman, 1995). The ubiquity of p40 in eukaryotes and the similarity among the proteins for which sequences have been deduced suggest that p40 plays a fundamental role in cell metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…Initial studies identified p40 as the 67-kD laminin receptor found in vertebrate basement membranes (Wewer et al, 1986;Yow et al, 1988), although subsequent investigations have called into question the relationship between p40 and the receptor (Grosso et al, 1991;Yang et al, 1992). Lower organisms and plants are not known to contain laminin, and the majority of p40 from several species has been clearly shown to be in the cytoplasm, either in association with ribosomes (McCaffery et al, 1990;Auth and Brawerman, 1992;Davis et al, 1992;García-Hernández et al, 1994;Togho et al, 1994;Rosenthal and Wordeman, 1995) or the cytoskeleton (Keppel and Schaller, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…55 While lacking the posttranslational processing that takes place in the native environment of eukaryotic cells, the bacterial recombinant protein appears to form a stable folded structure as evidenced by the formation of stable, protease-resistant fragments. 48 Trypsin digestion of the full-length protein results in the appearance of 1 major band at an apparent molecular weight of 23 kDa (B) and 4 lighter, less stable bands varying from 12.5 to 9 kDa (C to F) on SDS-PAGE (Fig.…”
Section: Limited Proteolysis Of Recombinant Lbpmentioning
confidence: 99%